(untitled) (Eurasian Scientific Herald, 2023)
Injuries of the spine are a severe type of injury, accompanied in most cases by the disability of patients. Objective of the study: To improve the results of surgical treatment of injuries and diseases of the spine using TPF systems. The results of 114 patients with injuries of the thoracic and lumbar spine were analyzed. Mechanism of injury: fall from a height - 88 patients, road injury - 33 patients. Of the total number of examined patients, 53 patients underwent conservative treatment and 61 patients underwent surgical treatment. 1 Fixation of the damaged segment of the spine with various types of metal structures (TPF) - 22 patients. 2 Decompressive laminectomy with revision of the spinal canal and spinal cord at the level of injury (without fixation of the spinal column) – 20 patients. 3 Decompressive laminectomy at the level of damage + revision of the epi- and subdural spaces of the spinal cord and, as the final stage of the operation, fixation with metal structures - 19 patients. Results: During the surgical interventions, during the revision, a complete anatomical rupture of the spinal cord was found in 9 patients, in 27 cases, a picture of hematomyelia and spinal cord contusion at the level of damage. Conclusions: 1 in the presence of symptoms of spinal cord injury, it is necessary to perform LE, revision of the spinal canal and spinal cord. 2, the most reliable fixation is achieved when using a construct for TPF, which makes it possible to activate the patients early